Three Attempts at Inflation Forecasting in Pakistan. (IMF Working Papers; Working Paper ;, 2005)
This paper presents three empirical approaches to forecasting inflation in Pakistan. The preferred approach is a leading indicators model in which broad money growth and private sector credit growth help forecast inflation. A univariate approach also yields reasonable forecasts, but seems less suited to capturing turning points. A vector autoregressive (VAR) model illustrates how monetary developments can be described by a Phillips-curve type relationship. We deal with potential parameter instability on account of fundamental changes in Pakistan's economic system by restricting our sample to more recent observations. Gregorian and Islamic calendar seasonality are addressed by using 12-month moving averages.